2012
DOI: 10.1177/2150135111425065
|View full text |Cite
|
Sign up to set email alerts
|

Fontan Procedure at 2,240 m Above Sea Level

Abstract: The modified Fontan procedure represents the final stage of reconstructive surgery for most patients with functionally univentricular hearts. Although outcomes following Fontan procedures performed at sea level are widely reported, less has been documented and reported concerning outcomes in regions at high altitude. To clarify the main features involved, we present our institutional experience with Fontan operations performed in Mexico city (2,240 m above the sea level), with an emphasis on historical evoluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Its indications, benefits, risks, and long-term effects are still, therefore, a matter of debate. 13 High altitude, however, poses particular problems for the Fontan population because fenestration, usually considered necessary in this setting, 4 can significantly worsen hypoxemia due to low atmospheric P o 2 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Its indications, benefits, risks, and long-term effects are still, therefore, a matter of debate. 13 High altitude, however, poses particular problems for the Fontan population because fenestration, usually considered necessary in this setting, 4 can significantly worsen hypoxemia due to low atmospheric P o 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Although a previous report of the Fontan procedure from a center in Mexico City noticed a decrease in mortality coincidentally in time with the implementation of a fenestration strategy, the study did not analyze other concomitant factors that could have contributed to the overall improvement of the results, as has taken place in most centers. 4 Since high altitude around 2,500 m does not seem to be associated with an increase in PVR, in this situation, fenestration could be used also only in a selective manner in, for other reasons, high-risk patients. In other words, we think this altitude should not be considered a high risk factor since PVR is most likely to be normal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Focusing on univentricular physiology patients, it has been suggested that Fontan and Glenn surgeries might be higher risk procedures and less amenable to EE when performed at high altitudes, due to the direct effects of low PO 2 on SaO 2 and to its potential secondary effects in increasing PVRs. 24,25 However, EE (if possible in the OR) in univentricular heart anatomy patients undergoing either Glenn or Fontan procedures is desirable due to the positive hemodynamic effects for this particular physiology. 26 29…”
Section: Commentmentioning
confidence: 99%
“…The most common defects were patent ductus arteriosus (PDA; about 2/3), atrial septal defects (ASDs; about 1/5), and ventricular septal defects (VSD; about 1/10) with the prevalence of CHD in girls being higher than in boys. The condition of high altitudes may also have some effect on two routine cardiac surgery operations, including Fontan and bidirectional Glenn's anastomosis, although a sum of factors should probably be taken into account (e.g., age) [6][7][8][9]. The Fontan procedure comprises any surgical operation that results in the blood flow of systemic venous blood to the lungs without passing through a ventricle, while the bidirectional Glenn is a common surgical fashion of the second stage of the total cavopulmonary connection (TCPC) surgery where the end of the superior vena cava (SVC) is connected to the side of the pulmonary artery (PA).…”
mentioning
confidence: 99%